Publishing a Research Article: A Dialogue between the Author and the Journal - S. A. Sheypak (Высшее образование в России)
The paper addresses concerns of preparing the research article for publication in a high-ranking international journal. The paper argues how to develop the competence which is required for successful manuscript submission in the international peer-review journal. The analysis of the reasons for rejecting the manuscript submitted in international journals suggests considering a successful submission through the dialogue between the author and the discourse community of the journal selected for publication. The publication competence of the author is considered as the author’s ability to construct his/her position in the text or authorial voice. Bakhtin’s concept of voice allows interpreting authorial positioning in the dialogue with the discourse community selected for submission. While only the author’s position in the article is intentionally aligned with the epistemological, discursive, and rhetorical boundaries of the discursive community of the journal, the author’s voice may be approved by the community through publication. The approach adopted in the paper is based on Swales’ concept of discourse community and the concept of author’s positioning in academic text suggested by Ivanič. The structure of authorial positioning in the article is developed by using Schmid’s model of the narrative text. The publication competence of the author confirms his/her ability to construct authorial voice, which requires firstly determining the boundaries of the discursive community selected for publication through reading. When the author aligns his/her position in the manuscript with the community boundaries, the author’s voice is addressed to the selected community and it is able to convince the community in the validity of the researcher’s results. In conclusion, the structure of authorial positioning in the research paper is suggested for designing the curriculum of academic writing for publication purposes (ERPP) which aims at successful interactions between the author and the journal community at all stages of manuscript elaboration.